Identification of late asthmatic reactions following specific inhalation challenge. (22nd July 2020) - Moore, Vicky C; Walters, Gareth Iestyn; Robertson, Alastair S; Burge, P Sherwood
Abstract : Specific inhalation challenge (SIC) is the reference standard for the diagnosis of occupational asthma. Current guidelines for identifying late asthmatic reactions are not evidence based. Objectives: To identify the fall in forced expiratory volume in 1 s (FEV1 ) required following SIC to exceed the 95% CI for control days, factors which influence this and to show how this can be applied in routine practice using a statistical method based on the pooled SD for FEV1 from three control days. Methods: Fifty consecutive workers being investigated for occupational asthma were asked to self-record FEV1 hourly for 2 days before admission for SIC. These 2 days were added to the in-hospital control day to calculate the pooled SD and 95% CI. Results: 45/50 kept adequate measurements. The pooled 95% CI was 385 mL (SD 126), or 14.2% (SD 6.2) of the baseline FEV1, but was unrelated to the baseline FEV1 (r=0.06, p=0.68), or gender, atopy, smoking, non-specific reactivity or treatment before or during SIC. Thirteen workers had a late asthmatic reaction with ≥2 consecutive FEV1 measurements below the 95% CI for pooled control days, 4/13 had <15% and 9/13 >15% late fall from baseline. The four workers with ≥2 values below the 95% CI all had independent evidence of occupational asthma. Conclusion: The pooled SD method for defining late asthmatic reactions has scientific validity, accounts for interpatient spirometric variability and diurnal variation and can identify clinically relevant late asthmatic reactions from smaller exposures. For baseline FEV1 <2.5 L, a 15% fall is within the 95% CI.